From pyroptosis, apoptosis and necroptosis to PANoptosis: A mechanistic compendium of programmed cell death pathways - Wang, Yaqiu; Kanneganti, Thirumala-Devi (Computational and structural biotechnology journal, 2021)
[Display omitted] Pyroptosis, apoptosis and necroptosis are the most genetically well-defined programmed cell death (PCD) pathways, and they are intricately involved in both homeostasis and disease. Although the identification of key initiators, effectors and executioners in each of these three PCD pathways has historically delineated them as distinct, growing evidence has highlighted extensive crosstalk among them. These observations have led to the establishment of the concept of PANoptosis, defined as an inflammatory PCD pathway regulated by the PANoptosome complex with key features of pyroptosis, apoptosis and/or necroptosis that cannot be accounted for by any of these PCD pathways alone. In this review, we provide a brief overview of the research history of pyroptosis, apoptosis and necroptosis. We then examine the intricate crosstalk among these PCD pathways to discuss the current evidence for PANoptosis. We also detail the molecular evidence for the assembly of the PANoptosome complex, a molecular scaffold for contemporaneous engagement of key molecules from pyroptosis, apoptosis, and/or necroptosis. PANoptosis is now known to be critically involved in many diseases, including infection, sterile inflammation and cancer, and future discovery of novel PANoptotic components will continue to broaden our understanding of the fundamental processes of cell death and inform the development of new therapeutics.